THE RELATION OF TAXATION TO THE HISTORY OF THE BALANCE SHEET. - Penndorf, B. (The Accounting Review, 1930)
Abstract This article focuses on the relation of taxation to the history of the balance sheet. The census which was introduced by the Emperor Augustus at the time of the birth of Christ was of great importance, for it was intended to obtain a firm financial basis for expenses; consequently, it laid the foundation of a budget and the proportional distribution of taxes among those who were liable to pay. The first entries were made upon wooden boards coated with wax, which were put together in the shape of a book, originally being called "caudex" and after the introductions of parchment, "charta." The taxpayer had then to declare upon oath that he had made no false entries. Citizens shared political authority according to the amount of property declared and the Roman, therefore, kept not only exact accounts of their daily receipts and expenditures, but also exact statements of their property. The relation between balance sheet and taxation can best be explained by. an examination of the business books and tax returns of the great Florentin banking house of the Medici.